(untitled) (International Research in Economics and Finance, 2018)
The analysis of network of 30 US industries shows the leading role of finance industry. Following are major findings and observations: 1) we show that leading industry in economy changes over time as the U.S. industry structure changes over time. Finance industry plays a leading role of net information source over the sample period of 1930-2014, and the importance of finance industry starts to dominate from 1975. 2) Even when finance industry is not ranked as the strongest source of information, the finance industry dominates in the industry network when the net information flows are adjusted by the value added of finance in the GDP. 3) Differences of strength of directed connectedness (ASDC) of source and sink industries signal potential disturbance in the network of industries.